HERVd: database of human endogenous retroviruses - Paces, Jan; Pavlícek, Adam; Paces, Václav (Nucleic acids research, 2002)
The human endogenous retroviruses database (HERVd) is maintained at the Institute of Molecular Genetics, Academy of Sciences of the Czech Republic, and is accessible via the World Wide Web at http://herv.img.cas.cz. The HERVd provides complex information on and analysis of retroviral elements found in the human genome. It can be used for searches of individual HERV families, identification of HERV parts, graphical output of HERV structures, comparison of HERVs and identification of retrovirus integration sites.
Keywords: Database Management Systems; internet; endogenní retroviry; databáze nukleových kyselin; genom lidský; Information Storage and Retrieval; Databases, Nucleic Acid; molekulární evoluce; Evolution, Molecular; Genome, Human; ukládání a vyhledávání informací; Internet; systémy řízení databází; Endogenous Retroviruses; Virus Integration; Animals; lidé; Humans; zvířata; myši; integrace viru; Mice